Quality of Literacy Courses in Online Blended Learning: Analysis of Curriculum, Teaching Learning Environment, Evaluation System and Feedback - Alamgeer Siddiqi (IJLTP, 2025)
This study analyzed perceptions of students towards online blended learning environment in which quality of literacy courses in online blended learning was analyzed in terms of quality of curriculum, teaching learning environment, feedback and evaluation system. As we all know, this is technology-oriented era and world has transformed into techno-village in which every field of life is influenced with technological interventions. Education and literacy are also impacted by technology drive. Online education is entirely based upon technology gadgets where literacy initiatives are influenced. To achieve the goal of this study, data was collected through survey by administering questionnaire from randomly selected sample of 100 postgraduate university students. The findings gave positive perceptions towards quality curriculum, and teaching-learning environment. However, respondents indicated unsatisfactory provisions and use of ICT tools and learning resources indicating dominance of teacher in selection of teaching methods, a smaller amount of ICT use, strain in courses’ completion process and delayed declaration of exam result. The study recommended that the online blended literacy environment should foster use of proper ICT tools, students’ engagement, use of multiple assessment and feedback activities to enhance quality of online blended literacy environment in a variety of ways.